Fabrication, rheological analysis, and in vitro characterization of in situ chemically cross‐linkable thermogels as controlled and prolonged drug depot for localized and systemic delivery. (17th December 2018) - Khan, Samiullah; Akhtar, Naveed; Minhas, Muhammad Usman
Abstract : 5‐Fluorouracil (5‐FU) is widely used against many types of solid cancer in clinics. However, because of its limitations such as short half‐life, poor oral absorption and rapid clearance by dihydropyrimidine dehydrogenase have limited its applications. In current study, new in situ chemically grafted thermogels for prolonged drug release are formed on the basis of poloxamer 407 (PF127) and carboxymethyl chitosan (CMCS) using glutaraldehyde as cross‐linking agent. The phase transition from sol to gel state at body temperature was confirmed by tube titling, rheological analysis, and optical transmittance determinations. Swelling and drug release experiments conducted at various pH and temperature demonstrated that developed formulations are thermoresponsive with maximum swelling and release below critical gelation temperature (CGT) (pH 7.4, 25°C). Cells growth inhibition study confirmed the biocompatibility of thermogels against L929 cell lines. Methyl thiazolyl tetrazolium (MTT) assay confirmed that 5‐FU–loaded thermogels have the potential to cause cells death against HeLa and MCF‐7 cancer lines. The IC50 values calculated for pure 5‐FU solution (27 ± 0.81 μg/mL for HeLa and 24 ± 0.58 μg/mL for MCF‐7) were found higher in comparison with 5‐FU–loaded thermogels, against HeLa (17 ± 0.39 μg/mL) and MCF‐7 (14 ± 0.67 μg/mL). Fourier transform infrared (FTIR) confirmed the new structure formation and chemical grafting between PF127 and CMCS. Thermogravimetric (TG) and differential scanning calorimetry (DSC) analyses proved the phase transition around physiologic temperature range, while scanning electron microscopy (SEM) analysis displayed the presence of connected pores in the cross section of thermogels facilitating the uptake of solvents and drug particles. Altogether, results concluded that developed chemically grafted thermogels can be used in vivo for prolonged drug release after subcutaneous administration.